Dentinal defects induced by 6 different endodontic files when used for oval root canals: an in vitro comparative study - Ajinkya M Pawar; Bhagyashree Thakur; Anda Kfir; Hyeon-Cheol Kim (Restorative Dentistry & Endodontics, 2019)
ObjectivesTo compare the formation of dentinal defects using stainless-steel hand K-files (HFs), rotary files, reciprocating files, and Self-Adjusting File (SAF), when used for oval root canals.Materials and MethodsOne hundred and forty extracted human mandibular premolar with single root and oval canal were selected for this study. Oval canals were confirmed by exposing to mesio-distal and bucco-lingual radiographs. Teeth with open apices or anatomic irregularities were excluded. All selected teeth were de-coronated perpendicular to the long axis of the tooth, leaving roots segments approximately of 16 mm in length. Twenty teeth were left unprepared (control), and the remaining 120 teeth were divided into 6 groups (n = 20) and instrumented using HF (size 40/0.02), Revo-S (RS; size 40/0.06), ProTaper NEXT (PTN; size 40/0.06), WaveOne (WO; size 40/0.09), RECIPROC (RC; size 40/0.06), and the SAF (2 mm). Roots were then sectioned 3, 6, and 9 mm from the apex, and observed under stereomicroscope, for presence of dentinal defects. “No defect” was defined as root dentin that presented with no visible microcracks or fractures. “Defect” was defined by microcracks or fractures in the root dentin.ResultsThe control, HF, and SAF did not exhibit any dentinal defects. In roots instrumented by RS, PTN, WO, and RC files exhibited microcracks (incomplete or complete) in 40%, 30%, 55%, and 50%, respectively.ConclusionsThe motor-driven root canal instrumentation with rotary and reciprocating files may create microcracks in radicular dentine, whereas the stainless-steel hand file instrumentation, and the SAF produce minimal or less cracks.